A simple preparation method for CLEM using pre-embedding immunohistochemistry with a novel fluorescent probe and stable embedding resin. (22nd January 2021) - Kanemaru, Takaaki; Kondo, Teruyoshi; Nakamura, Kei-ichiro; Morimoto, Hiroyuki; Nishi, Kentaro; Isobe, Shin-ichiro
Abstract: Correlative light and electron microscopy (CLEM) is an excellent approach for examining the cellular localization of biomolecules. Here, we developed a simple method for CLEM by combining pre-embedding immunohistochemistry with a novel fluorescent probe, namely Fluolid NS Orange, and an embedding resin called ʻDurcupan ™ ʼ. Specimens were embedded in Durcupan ™ or LR White after immunolabeling and post-fixation using glutaraldehyde and osmium tetroxide. Next, ultrathin sections were prepared on a finder grid with navigation markers. The section of the specimen embedded in Durcupan ™ was found to be more stable against electron beam irradiation than specimens embedded in LR White. A fluorescence light microscopy image and a transmission electron microscopy (TEM) image, at wide-field, and low magnification, were independently obtained with the same ultrathin section. Using the three corners between finder grid bars as landmarks, fluorescence light microscopy images were superimposed with wide-field, low-magnification TEM images to identify the region of interest, which was subsequently enlarged to ascertain cellular structures localized beneath fluorescent signals. However, the enlarged TEM images appeared blurred, and fluorescence signals had a hazy appearance. To resolve this, the enlarged TEM images were replaced by high-resolution TEM images focused directly on the region of interest, thereby facilitating the collection of high-resolution CLEM images. The simple sample processing method for CLEM using osmium-resistant Fluolid NS Orange and electron beam damage-resistant Durcupan™ allowed the determination of the precise localization of fluorescence signals at subcellular levels.